2015
DOI: 10.1016/j.otsr.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of dystonia in extensor hallucis longus and digitorum muscles with neurotomy of the branches of the deep fibular nerve: Preliminary results

Abstract: Deep fibular nerve neurotomy for the EHL and/or EDL branches seems to be an effective treatment for extension dystonia of the hallux and/or other toes and its consequences for the adult neurological patient. However, these encouraging preliminary results should be confirmed by prospective, longer-term studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The ultimate consequence of this situation is the activation of further nociceptors in the muscle through the release of bradykinin. However, these inflammatory factors can further aggravate the occurrence of muscle spasms [7] . Intramuscular injection of botulinum toxin blocks the neuromuscular transmission pathway and blocks this undesirable cycle.…”
Section: Resultsmentioning
confidence: 99%
“…The ultimate consequence of this situation is the activation of further nociceptors in the muscle through the release of bradykinin. However, these inflammatory factors can further aggravate the occurrence of muscle spasms [7] . Intramuscular injection of botulinum toxin blocks the neuromuscular transmission pathway and blocks this undesirable cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In the final analysis, botulinum toxin type A is a poison, but it is used as a medicine. Studies have shown that after entering the human body, botulinum toxin type A can release toxin proteins and prevent the transmission of neuromuscular signals, which is clinically effective [10] . Botulinum toxin type A needs to be injected with normal saline.…”
Section: Table 4: Comparison Of Dorsiflexion Angles Of Both Feet Befo...mentioning
confidence: 99%